Determination of 10 Tetracycline Antibiotics in Fruit Products and Meat Sauce by QuEChERS with Ultra Performance Liquid Chromatography-Triple Quadrupole Tandem Mass Spectrometry - Yue GU; Huixin TANG; Shuo LI; Ling MA; Ke WANG; Lili YANG (Shipin gongye ke-ji, 2023)
A method for the determination of 10 tetracycline antibiotics in fruit products and meat sauce was established by QuEChERS coupled with ultra performance liquid chromatography-triple quadrupole tandem mass spectrometry (UPLC-MS/MS). The optimal experimental conditions were determined by optimizing the mass spectrometric parameters, chromatographic conditions and pre-treatment techniques. The samples were extracted by 0.2% formic acid acetonitrile under ultrasonication, and then purified with PSA for fruit products and C18 for meat sauce. The target analytes were separated on a ZORBAX SB-Aq column (2.1 mm×150 mm, 3.5 μm), and detected by UPLC-MS/MS. The results demonstrated that the 10 tetracycline antibiotics showed good linearity in the respective linear range with the correlation coefficients (r) higher than 0.999. The limits of detection (S/N=3) were 0.09~3.92 μg/kg, and the limits of quantification (S/N=10) were 0.31~13.05 μg/kg. The average recoveries at three different spiked levels of 75, 300 and 750 μg/kg ranged from 70.0% to 101.0% with the relative standard deviation (RSD) of 1.0%~10.3% (n=7). The method is sensitive, simple and suitable for the rapid and simultaneous detection of 10 tetracycline antibiotics in fruit products and meat sauce.